Dinamika Manajemen Waktu Mahasiswa Aktivis: Menyeimbangkan Prestasi Akademik dan Tanggung Jawab Organisasi - Evy Nurmiati; Oktariani, Chalifa Chairunnisa; Akram Faqih, Nizham; Wahyu Kusuma Putra (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
Modern higher education demands students to possess a balance between intellectual excellence and social maturity through organizations. However, the reality at UIN Syarif Hidayatullah Jakarta shows a sharp priority conflict between technical curriculum demands and a strong organizational culture, often leading to academic procrastination. This study aims to evaluate the time management dynamics of student activists and their impact on technical competence mastery. Using a descriptive qualitative approach, this study combines participatory observation data over one semester with a literature study of 10 journal articles (2021-2025). Research findings reveal that time inefficiency in organizational activities correlates with "Cramming System" (SKS) behavior, which significantly degrades the quality of programming hardskills. Nevertheless, supporting literature confirms that organizations remain effective incubators for leadership soft skills if managed with the right strategies. This article recommends the adoption of the Eisenhower Matrix discipline and the Deep Work concept to prevent burnout and maintain academic integrity.